2007
DOI: 10.1095/biolreprod.106.058594
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways for Germ Cell Death in Adult Cynomolgus Monkeys (Macaca fascicularis) Induced by Mild Testicular Hyperthermia and Exogenous Testosterone Treatment1

Abstract: Male contraception has focused, to a great extent, on approaches that induce azoospermia or severe oligospermia through accelerated germ cell apoptosis. Understanding the specific steps in the germ cell apoptotic pathways that are affected by male contraceptives will allow more specific targeting in future contraceptive development. In this study, we have used a nonhuman primate model to characterize the key apoptotic pathway(s) in germ cell death after mild testicular hyperthermia, hormonal deprivation, or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
4
49
1
1
Order By: Relevance
“…The subcellular redistribution of Bax and the increase in Bcl-2 expression in heat-treated testes suggest an involvement of Bcl-2 family members in heat-induced germ-cell apoptosis [45]. Our in vivo experiments also demonstrated that the heat-induced changes in the expression of caspase 2 [46], nitric oxide synthase [47] and various heat shock proteins (HSP) [48] in the testis of adult monkeys were all reversible [49]. HSP70-2 expression was almost unchanged at an early stage of germ cell apoptosis in the cryptorchid testis on day 5, and dropped dramatically, along with loss of apoptotic germ cells on day 10 after the procedure.…”
Section: Heat-induced Germ Cell Apoptosissupporting
confidence: 55%
“…The subcellular redistribution of Bax and the increase in Bcl-2 expression in heat-treated testes suggest an involvement of Bcl-2 family members in heat-induced germ-cell apoptosis [45]. Our in vivo experiments also demonstrated that the heat-induced changes in the expression of caspase 2 [46], nitric oxide synthase [47] and various heat shock proteins (HSP) [48] in the testis of adult monkeys were all reversible [49]. HSP70-2 expression was almost unchanged at an early stage of germ cell apoptosis in the cryptorchid testis on day 5, and dropped dramatically, along with loss of apoptotic germ cells on day 10 after the procedure.…”
Section: Heat-induced Germ Cell Apoptosissupporting
confidence: 55%
“…Despite the evidence suggesting that T increases apoptotic cell death, [17][18][19][20] the present study suggests that the use of exogenous testosterone at supra physiological levels is safe regarding MI size, area of no-reflow and post-MI cardiac function. This study also suggests that supra physiological levels of testosterone may in fact be beneficial in the scope of creating an anti-arrhythmia setting by shortening the QTc interval.…”
Section: Discussioncontrasting
confidence: 80%
“…Some studies suggest positive cardiovascular effects of testosterone with regards to QT segment duration [12][13][14] and that higher testosterone levels are associated with a lower risk of cardiac mortality [15] and better functional capacity [16]. However, other evidence suggests that testosterone exerts a negative impact on the cardiovascular system with regards to apoptosis [17][18][19][20] and adverse cardiac events [21].…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of caspase 2 activation prevents heat-induced germ cell apoptosis in rats by suppressing the MAPK14 ( Johnson et al 2008;Li et al 2009a,b). Serine phosphorylation of Bcl-2 and activation of the MAPK14-mediated mitochondria-dependent pathway are critical for heat-induced male germ cell death in monkeys ( Jia et al 2007). …”
Section: Apoptosis In Male Germ Cellsmentioning
confidence: 99%